BENEFITS OF BEE CULTIVATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the conditions of Bukhara region, the increase in the weight of eggs laid by queens due to additional feeding of bee families for artificial breeding of queens from the bee family of the local population. The weight of a bee's egg is related to the quality of the queen's large number of eggs, the strength of the bee's family, the weight of the queen's bees, and the number of egg tubes in her ovary.